1982
DOI: 10.1111/j.1365-2125.1982.tb04935.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pretreatment with cimetidine on the bioavailability and disposition of atenolol and metoprolol.

Abstract: 1 Plasma levels of atenolol and metoprolol and their effects on exercise heart rate have been studied after oral administration of single doses of 100 mg of the two drugs in ordinary tablets alone and during concomittant cimetidine medication of 1 g per day.2 Cimetidine caused no significant changes in the bioavailability of any of the two p-adrenoceptor blockers and the rate of elimination of metoprolol was unaffected by the histamine H2-receptor blocker. A slight but significant increase in the elimination h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…These characteristics bestow on atenolol clinical relevance as a probe substrate more sensitive than metformin for assessing hOCT2 inhibitors in vitro. However, available DDI data did not suggest a positive in vivo interaction for atenolol and cimetidine (Houtzagers et al, 1982;Kirch et al, 1982;Mutschler et al, 1984). The total renal clearance of atenolol (∼168 ml/min) is only 1.4-fold of its glomerular filtration clearance (∼120 ml/min), suggesting that active tubular secretion only contributes to a minor (∼30%) part of atenolol total clearance.…”
Section: Discussionmentioning
confidence: 97%
“…These characteristics bestow on atenolol clinical relevance as a probe substrate more sensitive than metformin for assessing hOCT2 inhibitors in vitro. However, available DDI data did not suggest a positive in vivo interaction for atenolol and cimetidine (Houtzagers et al, 1982;Kirch et al, 1982;Mutschler et al, 1984). The total renal clearance of atenolol (∼168 ml/min) is only 1.4-fold of its glomerular filtration clearance (∼120 ml/min), suggesting that active tubular secretion only contributes to a minor (∼30%) part of atenolol total clearance.…”
Section: Discussionmentioning
confidence: 97%
“…Kirch et al (1982) gave metoprolol loomg twice daily to 6 male subjects together with cimetidine and found that the AUC of metoprolol increased from 1167 ± 192 to 1885 ± 343 ~g/L • h (p < 0.05) with no change in half-life or exerciseinduced tachycardia. In contrast, Houtzagers et al (1982) gave 7 subjects aged 29 to 68 years with underlying pathology a single oral dose of metoprolol 100mg on 2 occasions, alone and after long term administration of cimetidine (1 g/day). The AUC of metoprolol did not differ between the 2 occasions (3.98 ± 1.18 versus 4.2 ± 1.1 ~molfL·h).…”
Section: Metapralalmentioning
confidence: 91%
“…Daneshmend & (1984) 0.85 ± 0.13 1.41 ± 0.32b t (60) 1.17 ± 0.47 1.89 ± 0.84 b t (62) Kirch et al (1982) 1.1 ± 0.8 1.1 ± 0.7 Houtzagers et al (1982) 2.93 ± 0.95 3.2 ± 1.26 Duchin et al (1984) Kirch et al (1982) 0.53 ± 0.35 0.78 ± 0.39b t (46) Duchin et al (1984) ~ (32) Donn et al (1984) tional, these data are consistent with the findings of Reimann and co-workers. When Duchin et al (1984) gave a single dose of propranolol 80mg to a group of subjects, cimetidine increased the propranolol AUe from 531 to 775 Ilg/L· h (p < 0.05).…”
Section: Propranololmentioning
confidence: 97%
“…The co-administration of the H2-receptor antagonist cimetidine, another commonly used agent, has been shown by some workers to increase the bioavailability of the lipophilic cardioselective 3-adrenoceptor blocker metoprolol, but not that of the hydrophilic cardioselective B3-adrenoceptor blocker atenolol (Kirch et al, 1981). This work has not been confirmed by Houtzagers et al (1982).…”
Section: Introductionmentioning
confidence: 94%